Is there a cognitive advantage in inhibition and switching for bilingual children? A systematic review - Planckaert, Niels; Duyck, Wouter; Woumans, Evy (Frontiers in Psychology, 2023)
Several studies have pointed to beneficial effects of bilingualism on executive functioning. However, observations of these beneficial effects have at times proven difficult to reproduce. Moreover, findings of studies on cognitive effects of bilingualism have been contested altogether. These contradictory outcomes leave the research field of bilingualism at unease. In the present review article, we aim to give a systematic overview of previous research on bilingual advantages in inhibition and switching in children up to the age of 12. Particular attention is paid to the experimental tasks that have been applied and the persistence of possible effects throughout critical and post-critical periods for cognitive development in children. In doing so, the review gives an insight in both the validity and robustness of possible domain-general cognitive effects of bilingualism in children. Terminological issues are also discussed.